PENERAPAN PEMOTONGAN TUNJANGAN KINERJA UNTUK MENINGKATKAN KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA KAYU AGUNG - Muhammad Haidar Alfatih; Rini Rini; Muhammad Yusuf (Politeknik Negeri Sriwijaya, 2020)
This research was conducted at the Kayu Agung Tax Office and aims to determine: a). An overview of employees' perceptions about cutting performance allowances; b). Description of employee performance and c). The effect of cutting performance allowances on employee performance. This research method uses a quantitative approach with the type of correlation. The variables in this study are the deduction of performance allowances as the independent variable (X) and employee performance as the dependent variable (Y). The population in this study were 82 employees with a sample of 54.9% (45 employees) who were taken using the proportional random sampling technique. The data collection technique used observation and documentation questionnaire techniques. The data obtained as a result of the questionnaire were analyzed using descriptive and inferential statistics which had previously been tested for analysis requirements. In this study, the results obtained: a) Employees' perceptions regarding the deduction of the performance allowance of the majority strongly agree; b) employee perceptions regarding employee performance, the majority agree; c) There is a significant positive effect between cutting performance allowances on employee performance. Therefore it is advisable to the leadership of the Kayu Agung Tax Office, presumably strive to maintain their performance and even further improve by providing training, briefing and checking work again.